Safety of mechanical and manual chest compressions in cardiac arrest patients: A systematic review and meta-analysis. (December 2021) - Gao, Yanxia; Sun, Tongwen; Yuan, Ding; Liang, Huoyan; Wan, Youdong; Yuan, Bo; Zhu, Changju; Li, Yi; Yu, Yanwu
Abstract: Aim: Summarise the evidence regarding the safety of mechanical and manual chest compressions for cardiac arrest patients. Methods: Two investigators separately screened the articles of EMBASE, PubMed, and Cochrane Central databases. Cohort studies and randomized clinical trials (RCTs) that evaluated the safety of mechanical (LUCAS or AutoPulse) and manual chest compressions in cardiac arrest patients were included. A meta-analysis was performed using a random effects model to calculate the pooled odds ratios (ORs) and their 95% confidence intervals (CIs). The primary outcome was the rate of overall compression-induced injuries. The secondary outcomes included the incidence of life-threatening injuries, skeletal fractures, visceral injuries, and other soft tissue injuries. Results: The meta-analysis included 11 trials involving 2, 818 patients. A significantly higher rate of overall compression-induced injuries was found for mechanical compressions than manual compressions (OR, 1.29; 95% CI, 1.19–1.41), while there was no significant difference between the two groups in respect of the rate of life-threatening injuries. Furthermore, both modalities shared similar incidences of sternal fractures, vertebral fractures, lung, spleen, and kidney injuries. However, compared to mechanical compressions, manual compressions were shown to present a reduced risk of posterior rib fractures, and heart and liver lesions. Conclusions: The findings suggested that manual compressions could decrease the risk of compression-induced injuries compared to mechanical compressions in cardiac arrest patients. Interestingly, mechanical compressions have not increased the risk of life-threatening injuries, whereas additional high-quality RCTs are needed to further verify the safety of mechanical chest devices. Trial registry : INPLASY; Registration number: INPLASY2020110111; URL: https://inplasy.com/ .